Trauma-Informed Care for Children in the Child Welfare System: An Initial Evaluation of a Trauma-Informed Parenting Workshop. (May 2016) - Sullivan, Kelly M.; Murray, Kathryn J.; Ake, George S.
An essential but often overlooked component to promoting trauma-informed care within the child welfare system is educating and empowering foster, adoptive, and kinship caregivers (resource parents) with a trauma-informed perspective to use in their parenting as well as when advocating for services for their child. In this first evaluation of the National Child Traumatic Stress Network's trauma-informed parenting workshop ( Caring for Children who Have Experienced Trauma, also known as the Resource Parent Curriculum), participant acceptance and satisfaction and changes in caregiver knowledge and beliefs related to trauma-informed parenting were examined. Data from 159 ethnically diverse resource parents were collected before and after they participated in the workshop. Results demonstrate that kinship and nonkinship caregivers showed significant increases in their knowledge of trauma-informed parenting and their perceived self-efficacy parenting a child who experienced trauma. Nonkinship caregivers increased on their willingness to tolerate difficult child behaviors, whereas kinship caregivers did not show a significant change. Participants also demonstrated high levels of satisfaction with the workshop. Although these preliminary results are important as the first empirical study supporting the workshop's effectiveness, the limitations of this study and the directions for future research are discussed.